Light-assisted O-methylation of phenol with dimethyl carbonate over a layered double oxide catalyst. Issue 8 (26th March 2019) - Wang, Xiaoyu; Wang, Ruiyi; Gu, Xianmo; Jia, Jianfeng; Zheng, Zhanfeng
Abstract : Phenol molecules can absorb light to achieve excited states, which allow deprotonation to occur more readily. Abstract : Layered double oxides (LDOs) exhibit high catalytic activity in the O -methylation of phenol under light irradiation, owing to the synergy of the light absorption of phenol molecules to achieve excited states and the facilitated adsorption of reactant molecules by the acid–base pairs of Mg3 Al-LDO, both of which can promote phenol deprotonation.